Legal restrictions on patent ownership in Algerian law - Mermoune, Moussa (Journal of Human Sciences, 2021)
The task of the national legislator is not only to establish legal norms to ensure secure and maintain justice. It must also adopt laws that contribute to the advancemem and developme of society.The law in modern societies must serve their development to the same extent that it serves its traditional purposes of security, freedom and justice.The law on the protection of inventions and the rights deriving therefrom 1s one of the most related and relevant to the development and advancement of the Community, through some of  its provisions that take into account certain aspects that would guarantee the right of ownership of the patent of its social function and support the general economic interest.